(untitled) (Revista Electrónica Calidad en la Educación Superior, 2022)
In this paper, the contributions of university evaluation and accreditation processes of graduate programs in Argentina to the development of the teaching function are analysed. For this purpose, the reports issued by the peer evaluating committees of running graduate programs in political science and international relations fields, accredited during 2019-21 period, are examined to determine if they show observations that will allow to consolidate and improve the current teaching practices. To conclude, it is noted that the processes coordinated by the accreditation board are aimed at collecting the relevance of the professional background of the academic body with the assigned tasks and the students’ achievements, resulting in the continuous training of teachers and teaching strategies secondary issues.